Nitrogen-doped silicon-carbon negative electrode material for battery and preparation method of nitrogen-doped silicon-carbon negative electrode material
By introducing nitrogen doping and carbon cladding into silicon carbon materials, the problem of high expansion rate and resistivity of silicon carbon materials under fast charging and discharge conditions is solved, and a silicon carbon negative electrode material with high conductivity and stability is achieved, which improves the battery's magnification and fast charging performance.
Patent Information
- Application Number
- CN202411664153.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-25
AI Technical Summary
Under high current density or fast charging and discharging of silicon carbon materials, lithium ion embedding and deintercalation lead to severe internal stress changes in the electrode material, resulting in an increase in high expansion rate and resistivity, affecting the cycling performance and fast charging performance of the battery.
A nitrogen-doped porous graphene matrix and nitrogen-doped nanosilicon particles are used to form a silicon-carbon negative electrode material with a carbon coating layer. Nitrogen doping improves the conductivity of the material, and the carbon cladding enhances the stability of the material.
It reduces resistivity, improves conductivity and electrochemical stability, reduces the expansion of electrode materials, and improves the rate performance and fast charging performance of lithium-ion secondary batteries.
Smart Images

Figure BDA0005144191160000071 
Figure BDA0005144191160000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to a silicon-carbon negative electrode material for batteries and a preparation method thereof, an electrode, and a battery. Background Art
[0002] Secondary batteries have been widely used in portable electronic products. With the miniaturization of portable electronic products and the increasing demand for secondary batteries in the aviation, military and automotive industries, the capacity and energy density of batteries need to be greatly improved.
[0003] Silicon has a theoretical specific capacity of 4200mAh / g. It can store more lithium ions than graphite negative electrodes, and the battery energy density is relatively high, which effectively improves the endurance and mileage. Because of its high theoretical capacity, low lithium insertion and extraction potential, environmental friendliness, and abundant reserves, it is regarded as the most promising next-generation lithium battery negative electrode material.
[0004] The alloying reaction of lithium ions and silicon causes a large volume expansion, which will generate a large amount of shear stress and compressive stress, causing the material particles to break and blocking the direct transmission of electrons on the material particles. As the number of charge and discharge cycles increases, the impact of volume expansion becomes more severe, causing the material particles to break seriously or even pulverize, which in turn causes some materials to completely lose their electrochemical activity, resulting in reduced battery capacity and poor cycle performance. At the same time, during the first charging process of a lithium-ion battery, a solid electrolyte interface (SEI) film will form on the surface of the negative electrode, consuming a portion of the lithium ions, forming irreversible capacity, and resulting in low coulombic efficiency.
[0005] Due to the structural stability of carbon materials, the volume change during the charge and discharge process is relatively small, and it has good cycle stability. In addition, similar to the chemical properties of silicon, silicon and carbon are often compounded to achieve the purpose of improving the volume expansion effect of silicon and improving its electrochemical stability. For example, silane gas is thermally decomposed at high temperature to form a silicon element and filled into a carbon carrier with a porous structure to form a silicon-carbon composite material filled with nano-silicon. First, silicon-carbon materials have good thermal stability. Due to their unique crystal structure, silicon-carbon materials can maintain stable performance in high temperature environments without obvious structural changes or performance degradation. This makes silicon-carbon materials have broad application prospects in high temperature environments, such as high-temperature furnaces, aerospace and other fields. Secondly, silicon-carbon materials also have good corrosion resistance. Whether in acidic, alkaline or neutral environments, silicon-carbon materials can show excellent corrosion resistance and will not change their performance due to environmental changes. This characteristic makes silicon-carbon materials have wide application potential in chemical, metallurgical and other industries. In addition, silicon-carbon materials also have good conductivity and insulation. This makes silicon-carbon materials have a wide range of applications in electronics, electricity and other fields. Especially in the field of batteries, silicon-carbon materials are regarded as a new type of battery negative electrode material with great potential due to their high specific energy and high charge and discharge efficiency. With the rapid development of products such as electric vehicles and wearable devices, the application prospects of silicon-carbon materials in the field of batteries are becoming more and more broad. In terms of environmental protection and sustainable development, silicon-carbon materials also show great potential. Because silicon-carbon materials have good recyclability and reusability, they can effectively reduce resource consumption and environmental pollution. At the same time, silicon-carbon materials can also be combined with other materials to form new composite materials with higher performance and wider application.
[0006] However, the pore structure of silicon-carbon materials is easy for lithium ions to be embedded and de-embedded, especially under high current density or rapid charge and discharge conditions. Under these conditions, lithium ions may be embedded and de-embedded more quickly, resulting in more drastic stress changes inside the electrode material and volume changes, which leads to higher expansion rates. In addition, the deposition of nano-silicon will increase resistivity and reduce conductivity, which is not conducive to the de-embedsion of lithium ions. Summary of the invention
[0007] In order to solve the above-mentioned problems of high expansion rate and high resistance, the present invention provides a silicon-carbon negative electrode material for a battery and a preparation method thereof.
[0008] The silicon-carbon negative electrode material for a battery described in the present invention comprises a nitrogen-doped porous graphene matrix, nitrogen-doped nano-silicon particles and a carbon coating layer; the nitrogen-doped nano-silicon particles are dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene matrix; the carbon coating layer completely or partially covers the surface of the nitrogen-doped porous graphene matrix and / or the nitrogen-doped nano-silicon particles.
[0009] Nitrogen doping can increase the conductivity of silicon-carbon negative electrode materials. For porous graphene substrates, the introduction of N atoms during nitrogen doping may cause the breakage or recombination of CC bonds in the graphene lattice, thereby forming structural defects. Secondly, for nano-silicon, the incorporation of nitrogen atoms changes the energy band structure of silicon, increasing the concentration of carriers (electrons and holes) in the material. This reduces the resistivity, thereby improving the conductivity of silicon-carbon materials.
[0010] The nitrogen content of the silicon-carbon negative electrode material is 0.1%-7.0%. Within the nitrogen content range, the silicon-carbon negative electrode material of the present invention increases the concentration of carriers (electrons and holes) in the material, reduces the resistivity, and thus improves the conductivity of the silicon-carbon material. The nitrogen content of the silicon-carbon negative electrode material is preferably 0.3%-5.0%, more preferably 0.5% to 3.0%.
[0011] The silicon content of the silicon-carbon negative electrode material is 30%-70%. Within this silicon content range, the silicon-carbon negative electrode material of the present invention has a very high reversible capacity. The silicon content of the silicon-carbon negative electrode material is preferably 40%-60%, more preferably 45%-55%.
[0012] The specific surface area of the silicon-carbon negative electrode material is 100 m 2 / g or less. Within this specific surface area range, the side reactions occurring on the surface of the silicon-carbon negative electrode material particles of the present invention are relatively few and the stability is relatively high. The specific surface area of the silicon-carbon negative electrode material is preferably 80m 2 / g or less, more preferably 50m 2 / g or less, more preferably 30m 2 / g or less.
[0013] The resistivity of the silicon-carbon negative electrode material is 50 Ω·cm or less. Within the resistivity range, the lithium-ion secondary battery using the silicon-carbon negative electrode material of the present invention has good rate performance. The resistivity of the silicon-carbon negative electrode material is preferably 20 Ω·cm or less, and more preferably 10 Ω·cm or less.
[0014] The tap density of the silicon-carbon negative electrode material is 0.1-2.0 g / cm 3 Within this range, the silicon-carbon negative electrode material particles of the present invention undergo a cycle of lithium ion insertion and extraction, and the particles expand less and are not easily broken, so that the lithium ion secondary battery using the material has a small cycle expansion and a stable cycle. The tap density of the silicon-carbon negative electrode material is preferably 0.3-1.5 g / cm 3 , more preferably 0.5-1.1 g / cm 3 .
[0015] The present invention also provides a method for preparing the silicon-carbon negative electrode material for a battery, which comprises the following steps:
[0016] (1) simultaneously depositing silicon and nitrogen on a porous graphene substrate by a vapor deposition method to obtain a nitrogen-doped porous graphene substrate and nitrogen-doped nano-silicon particles dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene substrate;
[0017] (2) Covering the surface of the nitrogen-doped porous graphene matrix and / or the nitrogen-doped nano-silicon particles with a carbon layer completely or partially by vapor deposition.
[0018] The present invention also provides an electrode, which comprises the above-mentioned silicon-carbon negative electrode material for a battery or the silicon-carbon negative electrode material prepared using the above-mentioned method for preparing the silicon-carbon negative electrode material for a battery.
[0019] The present invention also provides a battery, which comprises the above-mentioned electrode.
[0020] Beneficial effects: The silicon-carbon negative electrode material for batteries of the present invention has an electrochemical characteristic of high ion conduction rate when in use, and a battery prepared using the negative electrode active material has high rate performance and excellent fast charging performance. DETAILED DESCRIPTION
[0021] The present invention will now be further described in detail by way of examples, but the present invention is not limited to the examples.
[0022] The present invention discloses a silicon-carbon negative electrode material for a battery, comprising a nitrogen-doped porous graphene matrix, nitrogen-doped nano-silicon particles and a carbon coating layer; the nitrogen-doped nano-silicon particles are dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene matrix; the carbon coating layer completely or partially covers the surface of the nitrogen-doped porous graphene matrix and / or the nitrogen-doped nano-silicon particles.
[0023] The method for preparing the silicon-carbon negative electrode material for a battery of the present invention comprises the following steps.
[0024] (1) A nitrogen-doped porous graphene substrate and nitrogen-doped nano-silicon particles dispersedly distributed in the interior and / or on the surface of the nitrogen-doped porous graphene substrate are prepared. In actual experiments, the nitrogen-doped nano-silicon particles may be naturally dispersed in at least one of the following three situations: "interior", "surface", or "interior and surface" of the nitrogen-doped porous graphene substrate.
[0025] First, a certain mass of porous graphene substrate is loaded into the reactor; inert protective gas is continuously introduced into the reactor; the speed of the reactor is adjusted and the furnace chamber heating system is started; when the insulation point is reached, the nitrogen-containing precursor and the silicon-containing precursor are simultaneously introduced into the deposition furnace until the insulation is completed. After the temperature drops to room temperature, a nitrogen-doped porous graphene substrate and nitrogen-doped nano-silicon particles dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene substrate are obtained. The reactor can be one or more of a CVD furnace and a fluidized bed. The inert protective gas is one or more of nitrogen, argon, hydrogen, helium, neon or krypton. The speed of the reactor is 1 to 40 Hz, preferably 5 to 35 Hz, and more preferably 10 to 30 Hz. The insulation temperature is 400°C to 1000°C, preferably 450°C to 900°C, and more preferably 500°C to 800°C. The above-mentioned insulation time is 10 to 1200 min, preferably 50-800 min, and more preferably 80 to 700 min. The flow rate of the above-mentioned nitrogen-containing precursor is 0.1 to 15 L / min, preferably 0.2-8 L / min, and more preferably 0.4 to 3 L / min. The flow rate of the above-mentioned silicon-containing precursor is 0.5 to 20 L / min, preferably 1-10 L / min, and more preferably 1.5 to 5 L / min. The above-mentioned nitrogen-containing precursor is one or both of nitrogen or ammonia. The above-mentioned silicon-containing precursor is a silicon-containing gas including one or more silane gases of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0026] (2) Using a vapor deposition method, a carbon coating layer is completely or partially covered on the surface of the nitrogen-doped porous graphene matrix and / or the surface of the nitrogen-doped nano-silicon particles.
[0027] On the basis of step (1), continue to heat up to the second insulation point, and continue to introduce a certain flow of carbon-containing precursor until the insulation ends. After cooling to room temperature, the material is discharged to obtain a silicon-carbon negative electrode material. The insulation temperature is 400°C to 1000°C, preferably 450°C to 900°C, and more preferably 550°C to 850°C; the insulation time is 30 to 600 min, preferably 60 to 480 min, and more preferably 120 to 360 min; the above-mentioned carbon-containing precursor is one or more of methane, ethane, propane, butane, acetylene and propylene.
[0028] Example 1-1
[0029] The specific surface area of the porous graphene substrate used is 1100 m 2 / g, particle size D50 is 10μm, tap density is 0.39g / cm 3, take 1kg of porous graphene matrix and place it in a fluidized bed, continue to introduce argon gas to maintain fluidized state and inert atmosphere. Turn on the heating, adjust the speed to 10Hz, and start introducing monosilane and nitrogen at 520℃ at the same time. The flow rate of monosilane is 2L / min, and the flow rate of nitrogen is 0.5L / min. The time for introducing monosilane is 210min, the time for introducing nitrogen is 75min, and the insulation time is 250min. After the insulation is completed, the temperature is raised to 580℃, and acetylene is started to be introduced. After the end, the heating is turned off and cooled to room temperature to obtain the silicon-carbon negative electrode material.
[0030] Performance Testing
[0031] For the obtained silicon-carbon negative electrode material, the silicon content was determined by Eltra's ELEMENTRAC CS-i high-frequency infrared carbon-sulfur analyzer; the nitrogen content was determined by Leco's ONH836 oxygen-nitrogen-hydrogen analyzer; the specific surface area of the negative electrode active material was tested by Quantachrome Instruments' NOVA 4200e specific surface area tester; and the resistivity was determined by Suzhou Jingge's ST2722-SD powder low-resistance tester.
[0032] Take 30 parts of the above silicon-carbon negative electrode material, 64 parts of artificial graphite, 2.5 parts of conductive additives, and 3.5 parts of binder, and apply them in an aqueous system, then dry and roll them to obtain a negative electrode sheet containing the silicon-carbon negative electrode material of the present invention. The negative electrode sheet is cut, vacuum-baked, wound together with the paired lithium cobalt oxide positive electrode sheet and diaphragm, and loaded into an aluminum-plastic shell of corresponding size, a certain amount of electrolyte is injected, degassed and sealed, and a lithium-ion full battery of about 3.2Ah is obtained after formation. The capacity and efficiency of the full battery at different rates are measured using the BTS-5V6A battery tester of Shenzhen Xinwell Electronics Co., Ltd., and the long-cycle stability is measured at 1C / 1C.
[0033] The silicon content of the silicon-carbon negative electrode material of this embodiment is measured to be 33.91%, the nitrogen content is 1.51%, and the specific surface area is 94.4 m 2 / g, and the resistivity is 0.6Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 86.2%, CCCCR is 85.4%, and the cycle retention rate is 81.4%. The results are shown in Table 1.
[0034] Example 1-2
[0035] The process of Example 1-2 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 290 min, the nitrogen introduction time is changed to 85 min, and the insulation time is changed to 350 min.
[0036] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 41.39%, the nitrogen content was 1.52%, and the specific surface area was 53.4 m 2 / g, and the resistivity is 2.5Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 92.9%, CCCCR is 89.8%, and the cycle retention rate is 85.2%. The results are shown in Table 1.
[0037] Examples 1-3
[0038] The process of Example 1-3 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 434 min, the nitrogen introduction time is changed to 100 min, and the insulation time is changed to 494 min.
[0039] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 51.27%, the nitrogen content was 1.48%, and the specific surface area was 24.9 m 2 / g, and the resistivity is 3.8Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 94.3%, CCCCR is 90.2%, and the cycle retention rate is 88.7%. The results are shown in Table 1.
[0040] Examples 1-4
[0041] The process of Example 1-4 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 640 min, the nitrogen introduction time is changed to 125 min, and the insulation time is changed to 700 min.
[0042] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 60.63%, the nitrogen content was 1.48%, and the specific surface area was 16.8 m 2 / g, and the resistivity is 4.3Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.1%, CCCCR is 89.4%, and the cycle retention rate is 78.5%. The results are shown in Table 1.
[0043] Examples 1-5
[0044] The process of Example 1-5 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 950 min, the nitrogen introduction time is changed to 162 min, and the insulation time is changed to 1010 min.
[0045] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 69.33%, the nitrogen content was 1.48%, and the specific surface area was 14.3 m 2 / g, and the resistivity is 15.9Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 84.7%, CCCCR is 82.2%, and the cycle retention rate is 72.6%. The results are shown in Table 1.
[0046] Example 2-1
[0047] The process of Example 2-1 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 399 min, the nitrogen introduction time is changed to 8 min, and the insulation time is changed to 459 min.
[0048] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.88%, the nitrogen content was 0.13%, and the specific surface area was 25.7 m 2 / g, and the resistivity is 3.7Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.6%, CCCCR is 83.6%, and the cycle retention rate is 87.6%. The results are shown in Table 1.
[0049] Example 2-2
[0050] The process of Example 2-2 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 400 min, the nitrogen introduction time is changed to 20 min, and the insulation time is changed to 460 min.
[0051] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.84%, the nitrogen content was 0.31%, and the specific surface area was 25.5 m 2 / g, and the resistivity is 3.6Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.6%, CCCCR is 85.4%, and the cycle retention rate is 88.1%. The results are shown in Table 1.
[0052] Example 2-3
[0053] The process of Example 2-3 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 402 min, the nitrogen introduction time is changed to 35 min, and the insulation time is changed to 462 min.
[0054] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.85%, the nitrogen content was 0.54%, and the specific surface area was 25.7 m2 / g, and the resistivity is 2.8Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.7%, CCCCR is 88.7%, and the cycle retention rate is 88.5%. The results are shown in Table 1.
[0055] Embodiment 2-4
[0056] The process of Example 2-4 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 405 min, the nitrogen introduction time is changed to 60 min, and the insulation time is changed to 475 min.
[0057] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.85%, the nitrogen content was 0.92%, and the specific surface area was 25.6 m 2 / g, and the resistivity is 2.3Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.9%, CCCCR is 89.3%, and the cycle retention rate is 89.3%. The results are shown in Table 1.
[0058] Embodiment 2-5
[0059] The process of Example 2-5 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 410 min, the nitrogen introduction time is changed to 100 min, and the insulation time is changed to 470 min.
[0060] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.85%, the nitrogen content was 1.52%, and the specific surface area was 25.7 m 2 / g, and the resistivity is 1.7Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 94.4%, CCCCR is 90.3%, and the cycle retention rate is 90.1%. The results are shown in Table 1.
[0061] Embodiment 2-6
[0062] The process of Example 2-6 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 413 min, the nitrogen introduction time is changed to 120 min, and the insulation time is changed to 473 min.
[0063] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.88%, the nitrogen content was 1.81%, and the specific surface area was 25.7 m 2 / g, and the resistivity is 1.5Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 94.3%, CCCCR is 89.6%, and the cycle retention rate is 89.4%. The results are shown in Table 1.
[0064] Embodiment 2-7
[0065] The process of Example 2-7 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 418 min, the nitrogen introduction time is changed to 160 min, and the insulation time is changed to 478 min.
[0066] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.88%, the nitrogen content was 2.39%, and the specific surface area was 25.5 m 2 / g, and the resistivity is 2.2Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 94.1%, CCCCR is 89.4%, and the cycle retention rate is 88.6%. The results are shown in Table 1.
[0067] Embodiment 2-8
[0068] The process of Example 2-8 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced simultaneously, the monosilane introduction time is changed to 423 min, the nitrogen introduction time is changed to 200 min, and the insulation time is changed to 483 min.
[0069] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 49.88%, the nitrogen content was 2.95%, and the specific surface area was 25.6 m 2 / g, and the resistivity is 2.7Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 93.2%, CCCCR is 89.0%, and the cycle retention rate is 87.3%. The results are shown in Table 1.
[0070] Embodiment 2-9
[0071] The process of Example 2-9 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 445 min, the nitrogen introduction time is changed to 360 min, and the insulation time is changed to 505 min.
[0072] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 50.00%, the nitrogen content was 5.06%, and the specific surface area was 25.6 m 2 / g, and the resistivity is 4.6Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 92.7%, CCCCR is 85.6%, and the cycle retention rate is 85.7%. The results are shown in Table 1.
[0073] Embodiment 2-10
[0074] The process of Example 2-10 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 464 min, the nitrogen introduction time is changed to 510 min, and the insulation time is changed to 570 min.
[0075] The same performance test was carried out, and it was found that the silicon content in the silicon-carbon negative electrode material of this embodiment was 50.01%, the nitrogen content was 6.87%, and the specific surface area was 25.7 m 2 / g, and the resistivity is 8.9Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 91.1%, CCCCR is 81.1%, and the cycle retention rate is 83.4%. The results are shown in Table 1.
[0076] Comparative Example 1
[0077] The process of Comparative Example 1 is similar to that of Example 1-1, except that when monosilane and nitrogen are introduced at the same time, the monosilane introduction time is changed to 950 min, the nitrogen introduction time is changed to 0 min, and the insulation time is changed to 1010 min.
[0078] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this comparative example was measured to be 70.37%, the nitrogen content was 0%, and the specific surface area was 14.5m 2 / g, and the resistivity is 30.7Ω·cm. The evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD (3C / 0.1C) is 82.9%, CCCCR is 77.6%, and the cycle retention rate is 67.8%. The results are shown in Table 1.
[0079] Table 1 Performance parameters of silicon-carbon negative electrode materials in various embodiments and comparative examples
[0080]
[0081]
[0082] As shown in Table 1, for porous graphene substrates, the introduction of N atoms during nitrogen doping may cause the breakage or recombination of CC bonds in the graphene lattice, thereby forming structural defects. Secondly, for nano-silicon, the incorporation of nitrogen atoms changes the band structure of silicon, increasing the concentration of carriers (electrons and holes) in the material. This reduces the resistivity, thereby improving the conductivity of the silicon-carbon material. In addition, when the silicon content, nitrogen content, specific surface area, and resistivity of the silicon-carbon negative electrode material are all in the optimal range, the full battery performance of the lithium-ion secondary battery using the silicon-carbon negative electrode material is in the optimal numerical range.
[0083] The above-mentioned technologies not specifically mentioned are all referred to the prior art.
[0084] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.
Claims
1. A silicon-carbon negative electrode material for a battery, characterized in that: The invention comprises a nitrogen-doped porous graphene matrix, nitrogen-doped nano-silicon particles and a carbon coating layer; the nitrogen-doped nano-silicon particles are dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene matrix; and the carbon coating layer completely or partially covers the surface of the nitrogen-doped porous graphene matrix and / or the nitrogen-doped nano-silicon particles.
2. The silicon-carbon negative electrode material for a battery according to claim 1, characterized in that: The silicon-carbon negative electrode material has a nitrogen content of 0.1%-7.0%, a silicon content of 30%-70%, a specific surface area of less than 100 m² / g, and a resistivity of less than 50 Ω·cm.
3. The silicon-carbon negative electrode material for a battery according to claim 2, characterized in that: The silicon-carbon negative electrode material has a nitrogen content of 0.3%-5.0%, a silicon content of 40%-60%, a specific surface area of 80 m² / g or less, and a resistivity of 20 Ω·cm or less.
4. The silicon-carbon negative electrode material for a battery according to claim 3, characterized in that: The silicon-carbon negative electrode material has a nitrogen content of 0.5% to 3.0%, a silicon content of 45% to 55%, a specific surface area of less than 50 m² / g, and a resistivity of less than 10 Ω·cm.
5. The silicon-carbon negative electrode material for a battery according to claim 4, characterized in that: The specific surface area is less than 30 m² / g.
6. The method for preparing a silicon-carbon negative electrode material for a battery according to any one of claims 1 to 5, characterized in that: The steps include: (1) simultaneously depositing silicon and nitrogen on a porous graphene substrate by a vapor deposition method to obtain a nitrogen-doped porous graphene substrate and nitrogen-doped nano-silicon particles dispersedly distributed inside and / or on the surface of the nitrogen-doped porous graphene substrate; (2) Covering the surface of the nitrogen-doped porous graphene matrix and / or the nitrogen-doped nano-silicon particles with a carbon layer completely or partially by vapor deposition.
7. An electrode, characterized in that: A silicon-carbon negative electrode material for a battery comprising any one of claims 1 to 5 or a silicon-carbon negative electrode material prepared using the method for preparing a silicon-carbon negative electrode material for a battery according to claim 6.
8. A battery, characterized in that: Comprising the electrode according to claim 7.